"Hey, let me hold your guns for a while": A qualitative study of messaging for firearm suicide prevention. (1st February 2019) - Pallin, Rocco; Siry, Bonnie; Azrael, Deborah; Knoepke, Christopher E.; Matlock, Daniel D.; Clement, Ashley; Ranney, Megan L.; Wintemute, Garen J.; Betz, Marian E.
Abstract : A recommended component of suicide prevention is encouraging at‐risk individuals to voluntarily and temporarily reduce access to firearms and other lethal methods. Yet delivering counseling on the topic can be difficult, given the political sensitivity of firearm discussions. To support such counseling, we sought to identify recommended framing and content of messages about reducing firearm access for suicide prevention. Through qualitative interviews with firearm owners and enthusiasts, we identified key points for use in framing (identity as a gun owner, trust, voluntary and temporary storage, and context and motivation) and specific content (preference for "firearm" over "gun, " and legal issues such as background checks for transfers). These findings build on prior work and should enhance efforts to develop and deliver effective, acceptable counseling and—ultimately—prevent firearm suicide.